Improving Indonesian Narrative Text Literacy Through Brainstorming Learning In Class V Students Elementary School - Kristinawati, Danik (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aspects of literacy skills are almost the same as Indonesian language skills, namely listening skills, reading skills, speaking skills, and writing skills. main sentences and even pouring them back into written or spoken form. with learning through Brainstorming to increase students' narrative text literacy, this study used Qualitative Descriptive Data Analysis Techniques, the actions taken by the teacher to Increase Narrative Text Literacy Brainstorming learning was considered successful.